Three Phase Induction Motor Control Using Programmable Logic Control With Star Method - Haris Mastain Arzaq (Procedia of Engineering and Life Science, 2021)
The rapid development of automation system is inseparable from the development of technology in the field of control. In its development, a Programmable Logic Controller (PLC) has been widely used on an industrial scale. PLC programmable can be used as a controller of three phase induction motor. If an error occurs, it can be quickly identified and the work function of each device can be monitored and will also be easier to develop a method of control in the industry. This situation led to many large industries using PLC for all control equipment. In this study created a system of control of three phase induction motor using Programmable Logic Controller (PLC) with the method of Star (Y). Inrush current when the displacement of the position of Star (Y) to Delta (Δ) is expected to be reduced. The results of the research that has been done the tool can work well and yield value in accordance with the theory. As well as a tool in the design of specialized trainer so it can be used as a learning media.